1974
DOI: 10.2135/cropsci1974.0011183x001400030033x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Anatomical Features of Alfalfa Leaves as Related to CO2 Exchange1

Abstract: Cuttings from alfalfa (Medicago sativa L. cv. ‘Mesa‐Sirsa’) genotypes which exhibited a wide range in leaflet size were grown under spaced‐planted and nonspaced‐planted conditions and used to determine the relation. ships between leaflet anatomy, leaflet morphology, and CO2 exchange. These same relationships were evaluated under controlled environmental conditions using alfalfa population MSE‐6 which has a broad germplasm base.Area per leaflet and leaflet width were negatively associated with photosynthetic ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…SLA is a parameter that can have a marked impact on the expansion of the leaf area and hence on dry matter accumulation, particularly, in the early stages of growth. SLA could impact on dry matter accumulation because of a negative association between SLA and net CO 2 exchange rate per unit leaf area (Khan and Tsunoda 1970;Delaney and Dobrenz 1976;Dornhoff and Shible 1976), but is more likely to have an impact through a positive association between SLA and the rate of leaf area expansion (Rawson et al 1987;Tollenaar 1989;Hay 1990;Solhaug 1991). As explained by Solhaug (1991), even though high SLA could be associated with reduced net assimilation rate (NAR), the greater leaf expansion associated with high SLA would generally more than compensate for reduced NAR.…”
Section: Discussionmentioning
confidence: 99%
“…SLA is a parameter that can have a marked impact on the expansion of the leaf area and hence on dry matter accumulation, particularly, in the early stages of growth. SLA could impact on dry matter accumulation because of a negative association between SLA and net CO 2 exchange rate per unit leaf area (Khan and Tsunoda 1970;Delaney and Dobrenz 1976;Dornhoff and Shible 1976), but is more likely to have an impact through a positive association between SLA and the rate of leaf area expansion (Rawson et al 1987;Tollenaar 1989;Hay 1990;Solhaug 1991). As explained by Solhaug (1991), even though high SLA could be associated with reduced net assimilation rate (NAR), the greater leaf expansion associated with high SLA would generally more than compensate for reduced NAR.…”
Section: Discussionmentioning
confidence: 99%
“…Positive associations between rate of net photosynthesis (P,) and S, have been recorded in ryegrass, oat, soybean and lucerne (Wilson and Cooper 1969;Dornhoff and Shibles 1970;Criswell and Shibles 1971;Delaney and Dobrenz 1974). Wilson and Cooper (1969) found that in ryegrass genotypes, temperature caused changes in leaf thickness and mesophyll cell size, but these changes were not closely associated with changes in potential P,.…”
Section: ("C)mentioning
confidence: 99%
“…In determining photosynthetic rates, leaf characters such as leaf weight and leaf area play a major role (Delaney and Dobrenz 1974). Specific leaf weight (SLW) is one leaf character correlated positively with carbon exchange rate (CER) (Delaney and Dobrenz 1974). but no relationship between leaf area (LA) and SLW was found in alfalfa (Bhagsari and Brown 1986).…”
Section: Introductionmentioning
confidence: 99%